Penerapan Pendekatan dan Metode yang Relevan dalam Pembelajaran Tari di SMP Negeri 5 Kota Solok - Indrayuda Indrayuda (Fakultas Bahasa dan Seni UNP, 2009)
This article discusses about application of approaches and method in dance learning regarded to be relevance with the situation and condition in the SMPN 5 Solok. This article is going to answer many problems existing in the school faced by the dance teachers of West Sumatera. The problem is that the teachers are often not able to catch the appropriate method in the application of dance learning as well as to measure the students’ creativity correctly. This case is caused by the in appropriate approach and method of learning used by the teachers and less of facilities available. Related to that problem, the dance teachers of SMPN 5 Solok city try to answer it through applying approach and method that they consider to be relevance to the condition and situation of the school. The teachers use persuasive, cooperative, and motivated approach to analyze the problem. The learning method used in this study is the combination, of exploration and appreciation method, and then this approach is finally done effectively and efficiently in the school. Keywords: The dance teachers, strategy and the dance learning method.